A new species of the Apionine genus Baltoconapium Legalov, 2020 (Coleoptera: Brentidae) from Baltic amber - Legalov, Andrei A. (Paleontological journal)
A new species of apionine weevil Baltoconapium vilhelmseni sp. nov. is described from Baltic amber. The new species differs from the only described member of this genus, B. anderseni (Voss, 1972), in having a narrower body, weakly convex elytra with greenish sheen, slightly convex elytral interstriae, a longer rostrum, and a smaller body size.